Utility of second trimester beta HCG levels in prediction of gestational hypertension: a prospective cohort study - Chowdhary, Heena; Khurshid, Rabia; Parveen, Shameema; Yousuf, Shagufta; Tali, Showkat Hussain; Shah, Zafar Amin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gestational hypertension is a significant threat both to maternal and fetal health. However, it is still a distant dream to predict accurately its occurrence in early pregnancy. Objective was to find out if β HCG levels determined between 13 to 20 weeks of gestation can be used as a predictor for gestational hypertension. Methods: This prospective observational cohort study was conducted from August 2014 to January 2016. Serum β HCG levels were determined at 13 to 20 weeks of gestation of 190 normotensive pregnant women attending the antenatal clinics. They were followed for the development of gestational hypertension till 40 weeks of gestation or delivery. Results: Out of the total 190 women, 25 (13.1%) developed gestation hypertension. Of those who developed gestational hypertension, 22 (88%) were having β HCG levels >2 MOM (p<0.001). Absolute β HCG levels (Mean±SD) were also significantly higher (54907±29509 V/S 41095±19103; p<0.001) in subjects who later developed gestational hypertension. Sensitivity, specificity, positive predictive value and the negative predictive value for β HCG at >2 MOM were 83.3, 96.9, 80.0 and 97.5 respectively (95% CI). Conclusions: Pregnant women with high Beta HCG levels in early pregnancy have significantly higher risk for development of gestational hypertension.